2020
DOI: 10.1097/phm.0000000000001659
|View full text |Cite
|
Sign up to set email alerts
|

The Physiatry Workforce in 2019 and Beyond, Part 2

Abstract: Objective The aim of this study was to assess the current and future adequacy of physiatrist supply in the United States. Design A 2019 online survey of board-certified physiatrists (n = 616 completed, 30.1% response) collected information about demographics, practice characteristics, hours worked, and retirement intentions. Microsimulation models projected future physiatrist supply and demand using data from the American Board of Physical Medicine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 14 publications
(29 reference statements)
2
16
0
Order By: Relevance
“…Rehabilitation medicine is still an underdeveloped field, and there may be a lack of doctors specializing in rehabilitation worldwide. It has been reported that the supply of BCPs in the US does not match the demand 14 ) . Moreover, in many countries, education and training opportunities in rehabilitation medicine are inadequate, and targeted investment may be necessary to improve the quality of rehabilitation services.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation medicine is still an underdeveloped field, and there may be a lack of doctors specializing in rehabilitation worldwide. It has been reported that the supply of BCPs in the US does not match the demand 14 ) . Moreover, in many countries, education and training opportunities in rehabilitation medicine are inadequate, and targeted investment may be necessary to improve the quality of rehabilitation services.…”
Section: Discussionmentioning
confidence: 99%
“…This will be 30% lower than the maximum of 537 SCIM board‐certified physicians that was reached in 2007. Dall et al 9 predicted an overall 25% increase in the physicial medicine and rehabilitation (PMR) workforce 2019–2030 using a “baseline scenario” model with a constant number of PMR residency training positions, with increased supply matching increased demand over time. This contrasts with our prediction of a modest decline over the same time period for SCIM providers, because of the projected decrease in physicians with P‐BC by 2030 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…A recent workforce modeling study concluded that the United States will continue to have a persistent shortfall of physiatrists unless there is a sufficient increase in physiatry residency and fellowship positions. 38 Furthermore, geographical imbalances continue to exist in part owing to the limited PM&R training opportunities in some areas of the United States (e.g., especially in rural areas). 38,39 In addition to expanding the number of residency and fellowships positions, physiatric educational programs must be flexible and focused on the success of current and future physiatrists.…”
Section: Education/learning Environmentmentioning
confidence: 99%